Detection of genes for fimbrial antigens and enterotoxins associated with Escherichia coli serogroups isolated from pigs with diarrhea. - Harel, J (1991)
A total of 1,226 Escherichia coli strains isolated from 1979 to 1989 from pigs with diarrhea were examined for serogroup and fimbrial antigen F4 (K88) production. Four main patterns of isolation of the various serogroups were observed, depending on the ages of the pigs from which isolates were obtained and the production of F4. In pattern I, serogroups O8:K"S16", O9:K35, O9/O101:K30, O9/O101:K103, O9 (group), O20:K101, and O64:K"V142" were predominant in pigs aged 0 to 6 days (41.9% of isolates) and were less frequent in pigs aged 7 to 27 days (24.6% of isolates) but were rarely found in pigs aged 28 to 60 days (4.0% of isolates). In pattern II, the F4-associated serogroups O8:K"4627", O157:K"V17", O149:K91, and O147:K89 were predominant in pigs aged 7 to 27 days (29.8% of isolates) and in pigs aged 28 to 60 days (35.0% of isolates). In pattern III, serogroups O8 (group), O115:K"V165", and O147:K89 were rarely isolated from pigs aged 0 to 6 days but were equally distributed in pigs aged 7 to 27 days (10.1% of isolates) and in pigs aged 28 to 60 days (10.9% of isolates). In pattern IV, serogroups O138:K81, O139:K82, O141:K85ac, O45:K"E65", and O26:K60 were most frequently isolated in pigs aged 28 to 60 days (19.3% isolates). Over the period from 1979 to 1989, the proportion of isolates belonging to serogroups of pattern II and the proportion of F4 isolates within the serogroup O157:K"V17" declined, whereas the proportion of isolates of serogroups O147:K89, O8:K"S16", and O9:K35 increased. For 228 isolates selected from the most important serogroups, good agreement was observed between the results of gene probes and immunofluorescence for the detection of fimbrial antigens F4 (K88), F5 (K99), F6 (987P), and F41 and between the results of gene probes and biological assays for the detection of heat-labile enterotoxin (LT) and heat-stable enterotoxins a and b (STa and STb). The STa gene was mostly associated with isolates of pattern I serogroups, which had the F5, F6, and F41 genes alone or in various combinations. The LT and/or STb genes, with the F4 gene, mostly were observed in isolates of pattern II serogroups. The STb gene alone was observed mostly in isolates of pattern III serogroups, although isolates were negative for all fimbrial antigen genes. Similarly, isolates of pattern IV serogroups were negative for all fimbrial antigen genes and rarely positive for the enterotoxin genes. However, verotoxin production was associated with isolates of serogroups O138:K81 and O139:K82. The most important pathotypes among enterotoxigenic isolates in this study were F4:LT:STb, F5:STa, STb, F5:F41:STa, F4:STb, F6, STa, and LT.